Mapping transcriptomic profiles of seminal vesiculitis and experimental verification - Chenkui Miao; Shaobo Zhang; Jiajin Wu; Meiling Bao; Zengjun Wang; Bianjiang Liu (Asian Journal of Urology)
Objective: Seminal vesiculitis is a prevalent infectious disease in the genitourinary system, but its intrinsic pathogenesis and molecular features remain unclear. Methods: In this study, we utilized a next-generation sequencing technology to demonstrate transcriptomic landscapes of clinical specimens from seminal vesiculitis patients. We identified enriched Go Ontology terms, pathway maps, processes, toxicity, and metabolic networks of seminal vesiculitis. Results: Glutathione S-transferase activity is highly enriched, indicating its essential role in the disease's development. Furthermore, we established inflammation models of the seminal vesicle and verified the crucial function of glutathione S-transferase activity in these models. Conclusion: Glutathione S-transferase serves an essential role in seminal vesiculitis patients. Our results shall provide a robust platform for further intensive studies of seminal vesiculitis.